Sexual Transcription Differences in Brachymeria lasus (Hymenoptera: Chalcididae), a Pupal Parasitoid Species of Lymantria dispar (Lepidoptera: Lymantriidae) - Liu, Peng-Cheng; Tian, Shuo; Hao, De-Jun (Frontiers in Genetics, 2019)
Sex differences in gene expression have been extensively documented, but little is known about these differences in parasitoid species that are widely applied to control pests. Brachymeria lasus is a solitary parasitoid species and has been evaluated as a potential candidate for release to control Lymantria dispar. In this study, gender differences in B. lasus were investigated using Illumina-based transcriptomic analysis. The resulting 37,453 unigene annotations provided a large amount of useful data for molecular studies of B. lasus. A total of 1416 differentially expressed genes were identified between females and males, and the majority of the sex-biased genes were female biased. Gene Ontology (GO) and Pathway enrichment analyses showed that 1) the functional categories DNA replication, fatty acid biosynthesis and metabolism were enhanced in females and that 2) the only pathway enriched in males was phototransduction, while the GO subcategories enriched in males were those involved in membrane and ion transport. In addition, thirteen genes involving transient receptor potential (TRP) channels were annotated in B. lasus. We further explored and discussed the functions of TRPs in sensory signalling of light and temperature. In general, this study provides new molecular insights into the biological and sexually dimorphic traits of parasitoids, which may improve the application of these insects to the biological control of pests.